Distinct Roles of Smooth Muscle and Non-muscle Myosin Light Chain-Mediated Smooth Muscle Contraction - Sun, Jie; Qiao, Yan-Ning; Tao, Tao; Zhao, Wei; Wei, Li-Sha; Li, Ye-Qiong; Wang, Wei; Wang, Ye; Zhou, Yu-Wei; Zheng, Yan-Yan; Chen, Xin; Pan, Hong-Chun; et al. (Frontiers in Physiology, 2020)
Both smooth muscle (SM) and non-muscle (NM) myosin II are expressed in hollow organs such as the bladder and uterus, but their respective roles in contraction and corresponding physiological functions remain to be determined. In this report, we assessed their roles by analyzing mice deficient of Myl9, a gene encoding the SM myosin regulatory light chain (SM RLC). We find that global Myl9-deficient bladders contracted with an apparent sustained phase, despite no initial phase. This sustained contraction was mediated by NM myosin regulatory light chain (NM RLC) phosphorylation by myosin light chain kinase (MLCK). NM myosin II was expressed abundantly in the uterus and young mice bladders, of which the force was accordingly sensitive to NM myosin inhibition. Our findings reveal distinct roles of SM RLC and NM RLC in SM contraction.